MODERN APPROACHES TO TERMINOLOGY (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the intensive processes of neologization in the Russian language, caused by the emergence of new objects anfd realities, influenced by globalization, the advancement of science and technology, and internationalization